2017
DOI: 10.1016/j.cub.2017.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Motor Activity Dependent and Independent Functions of Myosin II Contribute to Actomyosin Ring Assembly and Contraction in Schizosaccharomyces pombe

Abstract: SummaryCytokinesis depends on a contractile actomyosin ring in many eukaryotes [1, 2, 3]. Myosin II is a key component of the actomyosin ring, although whether it functions as a motor or as an actin cross-linker to exert its essential role is disputed [1, 4, 5]. In Schizosaccharomyces pombe, the myo2-E1 mutation affects the upper 50 kDa sub-domain of the myosin II heavy chain, and cells carrying this lethal mutation are defective in actomyosin ring assembly at the non-permissive temperature [6, 7]. myo2-E1 als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 21 publications
(29 reference statements)
6
44
0
2
Order By: Relevance
“…We find Spn3 near the membrane, consistent with its assembly into membrane-bound oligomers with additional septin subunits ( An et al, 2004 ). In addition to membrane-binding proteins, the C-terminal tail of the essential contractile ring myosin-II Myo2 ( Kitayama et al, 1997 ; Palani et al, 2017 ) is near the membrane, as was observed in cytokinesis precursor nodes ( Laporte et al, 2011 ; Laplante et al, 2016 ). The N-terminus of the formin Cdc12 is also found near the membrane, in accord with direct binding to the F-BAR domain of Cdc15 ( Willet et al, 2015b ; Carnahan and Gould, 2003 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We find Spn3 near the membrane, consistent with its assembly into membrane-bound oligomers with additional septin subunits ( An et al, 2004 ). In addition to membrane-binding proteins, the C-terminal tail of the essential contractile ring myosin-II Myo2 ( Kitayama et al, 1997 ; Palani et al, 2017 ) is near the membrane, as was observed in cytokinesis precursor nodes ( Laporte et al, 2011 ; Laplante et al, 2016 ). The N-terminus of the formin Cdc12 is also found near the membrane, in accord with direct binding to the F-BAR domain of Cdc15 ( Willet et al, 2015b ; Carnahan and Gould, 2003 ).…”
Section: Resultsmentioning
confidence: 96%
“…At similar intermediate distances from the membrane, we find the tail domains of two additional myosins that contribute to S. pombe cytokinesis: the non-essential myosin-II, Myp2 ( Bezanilla et al, 1997 ; Mulvihill and Hyams, 2003 ), as well as a myosin-V, Myo51 ( Win et al, 2001 ; Tang et al, 2016 ). Though both are non-essential, Myp2 is implicated in ring constriction ( Palani et al, 2017 ; Laplante et al, 2015 ) while Myo51 contributes to ring formation and constriction ( Tang et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cell biological work with budding yeast and theoretical modeling demonstrated that ring closure can be powered by the thermal ratcheting of non-motor 3 crosslinkers along depolymerizing F-actin (Mendes Pinto et al, 2012;Oelz et al, 2015). Similarly, in fission yeast, a motor-impaired NMM-II mutant that robustly crosslinks F-actin is sufficient for ring assembly (Palani et al, 2017). Collectively, these studies suggest that F-actin crosslinking promotes cytoskeletal remodeling during cytokinesis, and ring closure in animal and fungal cells.…”
Section: Introductionmentioning
confidence: 91%
“…Intermediate layer: accessory protein network individual CR components, particularly those required for CR formation, contribute to contraction (Mishra et al, 2013;Huang et al, 2016a;Chew et al, 2017;Palani et al, 2017). These studies defined the minimal requirements for CR contraction in this system as the presence of F-actin, myosin-II ATPase activity and a balance of actin-crosslinking proteins (Mishra et al, 2013); surprisingly, the actin severer cofilin is not essential.…”
Section: Mid1 Cdc12mentioning
confidence: 99%